Beamforming for Non-Orthogonal Multicast and Unicast Transmissions Based on Rate Splitting in Satellite-Terrestrial Integrated Network - Bensi ZHANG; Deyi PENG; Yun LI (天地一体化信息网络)
A non-orthogonal multicast and unicast transmission scenarios in the satellite-terrestrial integrated networks (STIN was considered), and a system model of joint multi-group multicast and unicast downlink transmitting was constructed.In order to improved the spectral effi ciency of STIN, a beamforming scheme that non-orthogonal transmission based on rate splitting was proposed, where a max-min fair (MMF) beamforming design problem was established to optimized transmit beamforming vector of base station and satellite respectively.And then, considered non-convex constraint caused by variable coupling in the problem, an iterative algorithm based on successive convex approximation to solved the optimization problem was proposed.Simulation results showed that our proposed scheme could improved eff ectively the MMF transmitting rate of the STIN in contrast with the traditional non-rate splitting and layer division multiplexing schemes.